Chemical constituents of Streptomyces sp. strain Al-Dhabi-97 isolated from the marine region of Saudi Arabia with antibacterial and anticancer properties - Naif Abdullah Al-Dhabi; Galal Ali Esmail; Abdul-Kareem Mohammed Ghilan; Mariadhas Valan Arasu; Veeramuthu Duraipandiyan; Karuppiah Ponmurugan (Elsevier, 2020)
Background: Unlike the terrestrial region, the microorganisms especially actinomycetes groups existing in the marine environment are important sources for the medically important drugs and other active compounds. Considering the importance of natural compounds from the marine actinomycetes, the present study proceeded to identify and characterize promising antibacterial and anticancer actinomycetes from the marine region of Saudi Arabia and to profile the individual chemical components. Methods: Antimicrobial, anticancer and chemical profiling were performed by broth microdilution, mitochondrial membrane potential assays and GC-MS analysis. Investigations were directed towards the isolation and characterization of active Streptomyces sp. strain Al-Dhabi-97. Results: The obtained results of the morphological, biochemical, physiological and molecular level studies of the isolate Al-Dhabi-97 showed similarity towards the species of Streptomyces. Gram positive bacteria such as Bacillus subtilis, Enterococcus faecalis, Staphylococcus epidermidis and Staphylococcus aureus showed MIC values of 500, 250, 125 and 62.5 μg/ml and Gram negative bacteria such as Pseudomonas aeruginosa, Klebsiella pneumonia, Escherichia coli and Salmonella paratyphi reported MIC values of 500, 500, 250 and >250 μg/ml in the antimicrobial studies. The results of anticancer studies showed that at 100 μg/ml, the extract showed maximum cell growth inhibition and exhibited 2.5% necrosis, 62.2% late apoptosis and 20.8% early apoptosis in COLO 320 DM and VERO cell lines respectively. Chemical profiling of the extract authenticated the presence of constituents such as 1-phenanthrenemethanol (46.64%), phthalic acid, di(2-propylpentyl) ester (26.97%), benzenebutanoic acid (3.37%), podocarp-7-en-3-one (2.68%), and indole-3-carboxaldehyde (1.11%) respectively. Conclusion: The present study concluded that Saudi Arabian marine region was a promising area for the identification of medically important natural products producing actinomycetes for antibacterial and anticancer drugs. Keywords: Marine actinomycetes, GC-MS, Antibacterial compounds, Anticancer compounds